Pelatihan Pemanfaatan Padlet sebagai Inovasi Media Pembelajaran Keterampilan Menulis bagi Guru Bahasa Indonesia SMA Pekanbaru - Amira Deani; Oki Rasdana; Adib Alfalah (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2026)
Writing is a demanding literacy skill for senior high school students, yet classroom instruction often still relies on conventional, minimally interactive methods. This community service activity strengthened Indonesian language teachers' competence in Pekanbaru in using Padlet as a collaborative medium for writing instruction. Twenty-eight teachers from public and private senior high schools participated in a three-stage workshop comprising feature orientation, individual and group design practice, and intensive technical mentoring. Evaluation used a pre-test and post-test of conceptual understanding, a digital self-efficacy questionnaire, and structured practice observation. Mean conceptual understanding increased from 78 to 85, while digital self-efficacy rose from 3.08 to 4.06 on a four-point scale. Participants produced Padlet boards for narrative, descriptive, and argumentative texts, including peer feedback and teacher rubric features. The results indicate improved confidence, creativity, and readiness to integrate digital technology into Indonesian language writing instruction.